High-strength screen cloth and preparation method thereof

By using modified glass fibers and specific polymer raw materials, high-strength mesh is prepared, which solves the shortcomings of traditional nylon mesh in terms of strength and aging resistance, and achieves higher mechanical properties and aging resistance, which is suitable for high-strength mesh. Application areas of performance requirements.

CN119392396APending Publication Date: 2025-02-07福建俊诚纺织有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411669996.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Traditional nylon mesh cloth has shortcomings in strength and aging resistance, especially in extreme conditions, which cannot meet higher strength requirements, which limits its application range.

Method used

High-strength is prepared by copolymerizing and modifying glass fibers by using raw materials such as caprolactam, p-phenylenediamine, adipic acid, biphthalic acid, modified monomers, modified glass fibers, antioxidants and lubricants. Net cloth.

Benefits of technology

It significantly improves the mechanical properties and aging resistance of the mesh, and is suitable for high-performance requirements such as construction engineering materials and special protective equipment, extending the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005145586920000201
    Figure BDA0005145586920000201
Patent Text Reader

Abstract

The invention relates to the technical field of textile materials, and particularly discloses high-strength screen cloth and a preparation method thereof. The high-strength screen cloth is prepared from the following raw materials: caprolactam, p-phenylenediamine, adipic acid, diphenyldicarboxylic acid, a modified monomer, zinc diethyl hypophosphite, divinyl benzene, modified glass fibers, an antioxidant and a lubricant. The preparation method comprises the following steps: preliminarily polymerizing caprolactam, p-phenylenediamine, adipic acid, biphenyldicarboxylic acid and the modified monomer, then adding the modified glass fiber, zinc diethyl hypophosphite and divinyl benzene for continuous reaction to obtain a polyamide copolymer, and finally performing melt spinning and weaving on the polyamide copolymer, the antioxidant and the lubricant to obtain the required high-strength mesh cloth. The high-strength screen cloth prepared by the invention has excellent mechanical properties and aging resistance, is suitable for being applied to the fields with high-performance requirements, such as constructional engineering materials and special protective equipment, and is high in practicability and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile materials, and more particularly to a high-strength mesh cloth and a preparation method thereof. Background Art

[0002] Nylon mesh is a textile material with a mesh structure made of nylon (polyamide) fibers. Due to its good air permeability, high wear resistance, light weight, and easy cleaning, nylon mesh has been widely used in many fields such as textiles and clothing, medical care, transportation, sports, construction, agriculture, and industry. With the advancement of synthetic fiber technology, nylon mesh has developed rapidly and has shown excellent performance in various application fields. However, the strength of traditional nylon mesh still needs to be further improved in some fields that require higher material properties, such as construction engineering materials and special protective equipment. This is mainly because the strength of traditional nylon fibers cannot meet higher requirements under certain extreme conditions, thus limiting its scope of application.

[0003] In the prior art, in order to improve the strength of nylon mesh, the method of adding reinforcing materials to nylon fibers is usually adopted. Although these reinforcing materials (such as glass fiber, carbon fiber, aramid fiber, etc.) can improve the strength of nylon fibers to a certain extent, they also bring some new problems. For example, the compatibility between reinforcing materials and nylon fibers is poor, and stress concentration is easily generated at the interface, resulting in a decrease in the mechanical properties of the material. In addition, the introduction of reinforcing materials may increase manufacturing costs and process complexity, which is not conducive to large-scale production and application.

[0004] In addition, nylon mesh is prone to aging during long-term use. This includes being susceptible to ultraviolet radiation under direct sunlight, causing the material to gradually degrade; being susceptible to oxidation reactions due to long-term contact with oxygen in the air; and being in harsh environments such as high temperature and high humidity, the molecular spacing of nylon materials will increase, and the crystallinity will decrease, resulting in problems such as decreased mechanical strength and heat resistance. These aging phenomena not only reduce the service life of nylon mesh, but also limit its application in certain special fields. Based on the above statements, the present invention proposes a high-strength mesh and a preparation method thereof. Summary of the invention

[0005] In order to solve the problems of poor strength and aging resistance of existing nylon mesh cloth, the present invention provides a high-strength mesh cloth and a preparation method thereof.

[0006] In a first aspect, the present invention provides a high-strength mesh cloth, which adopts the following technical solution:

[0007] A high-strength mesh cloth comprises the following raw materials in parts by weight: 24-32 parts of caprolactam, 12-18 parts of p-phenylenediamine, 38-45 parts of adipic acid, 15-20 parts of biphenyl dicarboxylic acid, 4.5-6.5 parts of modified monomer, 0.5-1 part of diethyl zinc hypophosphite, 0.3-0.8 part of divinylbenzene, 8-12 parts of modified glass fiber, 1-2 parts of antioxidant, and 0.8-1.2 parts of lubricant.

[0008] Preferably, the high-strength mesh comprises the following raw materials in parts by weight: 28 parts of caprolactam, 15 parts of p-phenylenediamine, 42 parts of adipic acid, 18 parts of biphenyl dicarboxylic acid, 5.5 parts of modified monomer, 0.8 parts of diethyl zinc hypophosphite, 0.5 parts of divinylbenzene, 10 parts of modified glass fiber, 1.5 parts of antioxidant, and 1 part of lubricant.

[0009] Preferably, the modified monomer comprises 2-phenylacrylic acid and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester in a mass ratio of 3-5:1.

[0010] Preferably, the modified glass fiber is prepared by the following method:

[0011] (1) adding glass fiber to aminosilane hydrolyzate, stirring for 3-5 hours, washing with water, and drying to obtain amino-treated glass fiber;

[0012] (2) adding the aminated glass fiber into a phosphorus trichloride-toluene solution, adding 4-dimethylaminopyridine, stirring and treating at a temperature of 78-88° C. for 7-9 hours, removing the solvent under reduced pressure, and vacuum drying to obtain modified glass fiber.

[0013] Preferably, in step (1), the mass ratio of glass fiber to aminosilane hydrolyzate is 1:5-7; in step (2), the mass ratio of amination glass fiber, phosphorus trichloride-toluene solution, and 4-dimethylaminopyridine is 10:30-50:1-2; and in the phosphorus trichloride-toluene solution, the volume ratio of phosphorus trichloride to toluene is 2-3:4-8.

[0014] Preferably, the aminosilane hydrolyzate in step (1) is prepared by the following method: γ-aminopropyltriethoxysilane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane are added to an ethanol solution, and stirred at a temperature of 50-70° C. for 1-2 hours to obtain an aminosilane hydrolyzate.

[0015] Preferably, the mass ratio of the γ-aminopropyltriethoxysilane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and the ethanol solution is 7:2-3:100; and the mass concentration of the ethanol solution is 65-85%.

[0016] Preferably, the antioxidant is at least one of antioxidant 1010, antioxidant 1098, and antioxidant 168; and the lubricant is at least one of polyethylene wax, calcium stearate, and zinc stearate.

[0017] In a second aspect, the present invention provides a method for preparing a high-strength mesh cloth, using the following technical solution:

[0018] A method for preparing a high-strength mesh cloth comprises the following steps:

[0019] S1. Weigh caprolactam, p-phenylenediamine, adipic acid, biphenyl dicarboxylic acid, modified monomer, zinc diethyl phosphite, divinylbenzene, modified glass fiber, antioxidant, and lubricant by weight for later use;

[0020] S2, caprolactam, p-phenylenediamine, 1 / 2 mass of adipic acid, biphenyl dicarboxylic acid, and modified monomer are added to a polymerization kettle, stirred and mixed, vacuumed, heated to 226-235°C under a protective gas environment, reacted for 5-7h, depressurized to normal pressure, added with remaining adipic acid, modified glass fiber, zinc diethyl hypophosphite, and divinylbenzene, heated to 242-248°C, and continued to react for 3-5h. After the reaction, the discharged material is cooled to obtain a polyamide copolymer;

[0021] S3, mixing a polyamide copolymer, an antioxidant, and a lubricant, melt-extrude, spin-form, and draw and stretch to obtain nylon fibers, twist the nylon fibers to form nylon braided wires, and braid the nylon braided wires to obtain a high-strength mesh.

[0022] Preferably, in step S3, the melting temperature is 245-255° C., the spinning temperature is 250-260° C., the spinning speed is 850-1050 m / min, the drawing speed is 450-650 m / min, and the drawing multiple is 4-6 times.

[0023] In summary, the present invention has the following beneficial effects:

[0024] 1. The present invention uses raw materials caprolactam, p-phenylenediamine, adipic acid, biphenyl dicarboxylic acid, and modified monomers for preliminary polymerization, and then adds modified glass fiber, diethyl zinc hypophosphite, and divinylbenzene for continuous reaction to obtain a polyamide copolymer, which is finally melt-spun and woven with an antioxidant and a lubricant to obtain the desired high-strength mesh cloth; caprolactam, as a basic monomer, provides the mesh cloth with good mechanical strength and wear resistance, and forms a copolymer with p-phenylenediamine, adipic acid, and biphenyl dicarboxylic acid, which can improve the arrangement and crystallinity of the polymer chain and significantly improve the mechanical properties and thermal stability of the polymer; the modified monomer introduces phenyl and hindered amine light-stabilizing groups, which significantly improves the aging resistance of the polymer; the modified glass The fiber is used as a reinforcing material, which can significantly improve the mechanical strength and rigidity of the polyamide copolymer. The modified glass fiber has good compatibility with the system, which can further improve the comprehensive performance of the prepared mesh cloth. The addition of diethyl zinc hypophosphite and divinylbenzene can form a cross-linked network structure with the system, which significantly improves the overall strength and heat resistance of the mesh cloth. At the same time, diethyl zinc hypophosphite is used as a flame retardant, which can also play a good flame retardant effect, and can further improve the thermal stability and anti-aging performance of the mesh cloth. The high-strength mesh cloth prepared by the present invention has excellent mechanical properties and aging resistance, is suitable for application in high-performance requirements such as construction engineering materials and special protective equipment, has high practicality, and has broad application prospects.

[0025] 2. The modified monomer of the present invention adopts a composite composition of 2-phenylacrylic acid and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester, wherein the phenyl group in the 2-phenylacrylic acid provides a rigid structure, so that the rigidity and mechanical strength of the copolymer are enhanced, and the presence of the phenyl structure can also improve the thermal stability and light stability of the polymer, so that the material can still maintain good performance under high temperature, ultraviolet irradiation and other environments; 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester can capture and neutralize free radicals, significantly improve the ultraviolet resistance of the polymer, and the hindered amine group can effectively prevent the degradation of the polymer under light, thereby extending the service life of the material; by controlling the composite ratio of the two, more comprehensive ultraviolet protection can be achieved, the overall stability of the polymer can be improved, the degradation caused by light can be reduced, and the service life of the material can be significantly extended.

[0026] 3. The present invention adds γ-aminopropyltriethoxysilane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to an ethanol solution to obtain an aminosilane hydrolyzate, and uses the aminosilane hydrolyzate to treat glass fibers to obtain amino glass fibers; the amino glass fibers are added to a phosphorus trichloride-toluene solution, and 4-dimethylaminopyridine is added and stirred to obtain modified glass fibers; the modified glass fibers prepared by the present invention have strong interfacial chemical bonding, can provide more chemical reaction sites, are easily chemically bonded with functional groups in a polyamide system, and significantly improve the compatibility of the glass fibers with the polyamide system; the modified glass fibers exhibit better stability at high temperatures, and can significantly improve the heat resistance and anti-aging properties of the mesh when combined with a polyamide system. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below with reference to the embodiments.

[0028] The materials and reagents used in the present invention, unless otherwise specified, can be obtained from commercial sources; among them, the glass fiber, brand Xianghui Technology, mesh number 800 mesh, density 2.2g / cm 3 , purchased from Shijiazhuang Xianghui Technology Co., Ltd.

[0029] Preparation Examples 1-3 and Comparative Preparation Examples 1-3 provide methods for preparing modified glass fibers.

[0030] Preparation Example 1

[0031] The modified glass fiber is prepared by the following method:

[0032] (1) controlling the mass ratio of γ-aminopropyltriethoxysilane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, and ethanol solution to be 7:2:100, adding γ-aminopropyltriethoxysilane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to an ethanol solution with a mass concentration of 65%, stirring at a temperature of 50° C. and a speed of 300 r / min for 2 h to obtain an aminosilane hydrolyzate; controlling the mass ratio of glass fiber and aminosilane hydrolyzate to be 1:5, adding glass fiber to the aminosilane hydrolyzate, stirring at room temperature for 5 h, washing with water, and drying at 80° C. to obtain an amino glass fiber;

[0033] (2) The mass ratio of the aminated glass fiber, phosphorus trichloride-toluene solution, and 4-dimethylaminopyridine was controlled to be 10:30:1, the aminated glass fiber was added to the phosphorus trichloride-toluene solution (the volume ratio of phosphorus trichloride to toluene was 2:4), 4-dimethylaminopyridine was added, and the mixture was stirred at 78° C. for 9 h, the solvent was removed under reduced pressure, and the mixture was vacuum dried at 80° C. to obtain a modified glass fiber.

[0034] Preparation Example 2

[0035] The modified glass fiber is prepared by the following method:

[0036] (1) controlling the mass ratio of γ-aminopropyltriethoxysilane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, and ethanol solution to be 7:2.5:100, adding γ-aminopropyltriethoxysilane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to an ethanol solution having a mass concentration of 75%, stirring at a temperature of 60° C. and a speed of 400 r / min for 1.5 h to obtain an aminosilane hydrolyzate; controlling the mass ratio of glass fiber to the aminosilane hydrolyzate to be 1:6, adding the glass fiber to the aminosilane hydrolyzate, stirring at room temperature for 4 h, washing with water, and drying at 90° C. to obtain an amino-treated glass fiber;

[0037] (2) The mass ratio of the aminated glass fiber, phosphorus trichloride-toluene solution, and 4-dimethylaminopyridine was controlled to be 10:40:1.5, the aminated glass fiber was added to the phosphorus trichloride-toluene solution (the volume ratio of phosphorus trichloride to toluene was 2.5:6), 4-dimethylaminopyridine was added, and the mixture was stirred at 83° C. for 8 h, the solvent was removed under reduced pressure, and the mixture was vacuum dried at 90° C. to obtain a modified glass fiber.

[0038] Preparation Example 3

[0039] The modified glass fiber is prepared by the following method:

[0040] (1) controlling the mass ratio of γ-aminopropyltriethoxysilane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, and ethanol solution to be 7:3:100, adding γ-aminopropyltriethoxysilane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to an ethanol solution having a mass concentration of 85%, stirring at a temperature of 70° C. and a speed of 500 r / min for 1 hour to obtain an aminosilane hydrolyzate; controlling the mass ratio of glass fiber to the aminosilane hydrolyzate to be 1:7, adding the glass fiber to the aminosilane hydrolyzate, stirring at room temperature for 3 hours, washing with water, and drying at 100° C. to obtain an amino-treated glass fiber;

[0041] (2) The mass ratio of the aminated glass fiber, phosphorus trichloride-toluene solution, and 4-dimethylaminopyridine was controlled to be 10:50:2, the aminated glass fiber was added to the phosphorus trichloride-toluene solution (the volume ratio of phosphorus trichloride to toluene was 3:8), 4-dimethylaminopyridine was added, and the mixture was stirred at 88° C. for 7 h, the solvent was removed under reduced pressure, and the mixture was vacuum dried at 100° C. to obtain a modified glass fiber.

[0042] Comparative Preparation Example 1

[0043] The modified glass fiber is prepared by the following method:

[0044] (1) controlling the mass ratio of γ-aminopropyltriethoxysilane to the ethanol solution to be 9:100, adding γ-aminopropyltriethoxysilane to an ethanol solution with a mass concentration of 65%, stirring at a temperature of 50° C. and a speed of 300 r / min for 2 h to obtain an aminosilane hydrolyzate; controlling the mass ratio of glass fiber to the aminosilane hydrolyzate to be 1:5, adding the glass fiber to the aminosilane hydrolyzate, stirring at room temperature for 5 h, washing with water, and drying at 80° C. to obtain an amino-treated glass fiber;

[0045] (2) The mass ratio of the aminated glass fiber, phosphorus trichloride-toluene solution, and 4-dimethylaminopyridine was controlled to be 10:30:1, the aminated glass fiber was added to the phosphorus trichloride-toluene solution (the volume ratio of phosphorus trichloride to toluene was 2:4), 4-dimethylaminopyridine was added, and the mixture was stirred at 78° C. for 9 h, the solvent was removed under reduced pressure, and the mixture was vacuum dried at 80° C. to obtain a modified glass fiber.

[0046] Comparative Preparation Example 2

[0047] The modified glass fiber is prepared by the following method:

[0048] (1) controlling the mass ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to the ethanol solution to be 9:100, adding 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to the ethanol solution with a mass concentration of 65%, stirring at a temperature of 50° C. and a speed of 300 r / min for 2 hours to obtain an aminosilane hydrolyzate; controlling the mass ratio of glass fiber to the aminosilane hydrolyzate to be 1:5, adding the glass fiber to the aminosilane hydrolyzate, stirring at room temperature for 5 hours, washing with water, and drying at 80° C. to obtain an amino-treated glass fiber;

[0049] (2) The mass ratio of the aminated glass fiber, phosphorus trichloride-toluene solution, and 4-dimethylaminopyridine was controlled to be 10:30:1, the aminated glass fiber was added to the phosphorus trichloride-toluene solution (the volume ratio of phosphorus trichloride to toluene was 2:4), 4-dimethylaminopyridine was added, and the mixture was stirred at 78° C. for 9 h, the solvent was removed under reduced pressure, and the mixture was vacuum dried at 80° C. to obtain a modified glass fiber.

[0050] Comparative Preparation Example 3

[0051] The modified glass fiber is prepared by the following method:

[0052] The mass ratio of γ-aminopropyltriethoxysilane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and ethanol solution is controlled to be 7:2:100, γ-aminopropyltriethoxysilane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane are added together to an ethanol solution with a mass concentration of 65%, and stirred at a temperature of 50°C and a speed of 300 r / min for 2 hours to obtain an aminosilane hydrolyzate; the mass ratio of glass fiber and aminosilane hydrolyzate is controlled to be 1:5, the glass fiber is added to the aminosilane hydrolyzate, stirred at room temperature for 5 hours, washed with water, and dried at 80°C to obtain a modified glass fiber.

[0053] Embodiment 1-3 provides a high-strength mesh cloth and a preparation method thereof.

[0054] Example 1

[0055] A high-strength mesh cloth comprises the following raw materials in parts by weight: 24 parts of caprolactam, 12 parts of p-phenylenediamine, 38 parts of adipic acid, 15 parts of biphenyl dicarboxylic acid, 4.5 parts of modified monomer, 0.5 parts of diethyl zinc hypophosphite, 0.3 parts of divinylbenzene, 8 parts of modified glass fiber, 1 part of antioxidant, and 0.8 parts of lubricant; wherein the modified monomer comprises 2-phenylacrylic acid and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester in a mass ratio of 3:1; the modified glass fiber is prepared by Preparation Example 1; the antioxidant is antioxidant 1010; and the lubricant is polyethylene wax.

[0056] A method for preparing a high-strength mesh cloth, characterized in that it comprises the following steps:

[0057] S1. Weigh caprolactam, p-phenylenediamine, adipic acid, biphenyl dicarboxylic acid, modified monomer, zinc diethyl phosphite, divinylbenzene, modified glass fiber, antioxidant, and lubricant by weight for later use;

[0058] S2, caprolactam, p-phenylenediamine, 1 / 2 of the mass of adipic acid, biphenyl dicarboxylic acid, and modified monomers are added to a polymerization kettle, the stirring speed is controlled to 500r / min, stirring and mixing for 40min, vacuumizing, heating to 226°C under nitrogen environment, reacting for 7h, depressurizing to normal pressure, adding the remaining adipic acid, modified glass fiber, diethyl zinc hypophosphite, and divinylbenzene, heating to 242°C, and continuing to react for 5h. After the reaction is completed, the discharged material is cooled to obtain a polyamide copolymer;

[0059] S3. Mix the polyamide copolymer, antioxidant and lubricant and stir for 40 minutes to obtain a mixture, control the melting temperature to 245°C, the spinning temperature to 250°C, the spinning speed to 850m / min, the pulling speed to 450m / min, the pulling multiple to 4 times, melt-extrude the mixture and then spin it into shape, pull and stretch it to obtain nylon fibers, twist the nylon fibers to form nylon braided wire, and weave the nylon braided wire with a plain weave structure to obtain a high-strength mesh.

[0060] Example 2

[0061] A high-strength mesh cloth comprises the following raw materials in parts by weight: 28 parts of caprolactam, 15 parts of p-phenylenediamine, 42 parts of adipic acid, 18 parts of biphenyl dicarboxylic acid, 5.5 parts of modified monomer, 0.8 parts of diethyl zinc hypophosphite, 0.5 parts of divinylbenzene, 10 parts of modified glass fiber, 1.5 parts of antioxidant, and 1 part of lubricant; wherein the modified monomer comprises 2-phenylacrylic acid and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester in a mass ratio of 4:1; the modified glass fiber is prepared by Preparation Example 2; the antioxidant is antioxidant 1098; and the lubricant is calcium stearate.

[0062] A method for preparing a high-strength mesh cloth, characterized in that it comprises the following steps:

[0063] S1. Weigh caprolactam, p-phenylenediamine, adipic acid, biphenyl dicarboxylic acid, modified monomer, zinc diethyl phosphite, divinylbenzene, modified glass fiber, antioxidant, and lubricant by weight for later use;

[0064] S2, caprolactam, p-phenylenediamine, 1 / 2 of the mass of adipic acid, biphenyl dicarboxylic acid, and modified monomers are added to a polymerization kettle, the stirring speed is controlled to 600r / min, stirring and mixing for 30min, vacuumizing, heating to 230°C under nitrogen environment, reacting for 6h, releasing the pressure to normal pressure, adding the remaining adipic acid, modified glass fiber, diethyl zinc hypophosphite, and divinylbenzene, heating to 245°C, and continuing to react for 4h. After the reaction is completed, the discharged material is cooled to obtain a polyamide copolymer;

[0065] S3. Mix the polyamide copolymer, antioxidant and lubricant and stir for 30 minutes to obtain a mixture, control the melting temperature to 250°C, the spinning temperature to 255°C, the spinning speed to 950m / min, the pulling speed to 550m / min, the pulling multiple to 5 times, melt-extrude the mixture and then spin it into shape, pull and stretch it to obtain nylon fibers, twist the nylon fibers to form nylon braided wire, and weave the nylon braided wire with a plain weave structure to obtain a high-strength mesh.

[0066] Example 3

[0067] A high-strength mesh cloth comprises the following raw materials in parts by weight: 32 parts of caprolactam, 18 parts of p-phenylenediamine, 45 parts of adipic acid, 20 parts of biphenyl dicarboxylic acid, 6.5 parts of modified monomer, 1 part of diethyl zinc hypophosphite, 0.8 parts of divinylbenzene, 12 parts of modified glass fiber, 2 parts of antioxidant, and 1.2 parts of lubricant; wherein the modified monomer comprises 2-phenylacrylic acid and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester in a mass ratio of 5:1; the modified glass fiber is prepared by Preparation Example 3; the antioxidant is antioxidant 168; and the lubricant is zinc stearate.

[0068] A method for preparing a high-strength mesh cloth, characterized in that it comprises the following steps:

[0069] S1. Weigh caprolactam, p-phenylenediamine, adipic acid, biphenyl dicarboxylic acid, modified monomer, zinc diethyl phosphite, divinylbenzene, modified glass fiber, antioxidant, and lubricant by weight for later use;

[0070] S2, caprolactam, p-phenylenediamine, 1 / 2 of the mass of adipic acid, biphenyl dicarboxylic acid, and modified monomers are added to a polymerization kettle, the stirring speed is controlled to 700r / min, and the mixture is stirred and mixed for 20min, and then vacuumed, heated to 235°C under a nitrogen environment, reacted for 5h, and depressurized to normal pressure, and the remaining adipic acid, modified glass fiber, diethyl zinc hypophosphite, and divinylbenzene are added, and the temperature is raised to 248°C, and the reaction is continued for 3h. After the reaction is completed, the discharged material is cooled to obtain a polyamide copolymer;

[0071] S3. Mix the polyamide copolymer, antioxidant and lubricant and stir for 20 minutes to obtain a mixture, control the melting temperature to 255°C, the spinning temperature to 260°C, the spinning speed to 1050m / min, the pulling speed to 650m / min, the pulling multiple to 6 times, melt-extrude the mixture and then spin it into shape, pull and stretch it to obtain nylon fibers, twist the nylon fibers to form nylon braided wire, and weave the nylon braided wire with a plain weave structure to obtain a high-strength mesh.

[0072] In order to verify the performance of the high-strength mesh obtained in Examples 1-3 of the present invention, the present invention sets up Comparative Examples 1-7.

[0073] Comparative Example 1

[0074] Comparative Example 1 is different from Example 1 only in that the modified monomer is only 2-phenylacrylic acid, as follows:

[0075] A high-strength mesh cloth comprises the following raw materials in parts by weight: 24 parts of caprolactam, 12 parts of p-phenylenediamine, 38 parts of adipic acid, 15 parts of biphenyl dicarboxylic acid, 4.5 parts of modified monomer, 0.5 parts of diethyl zinc hypophosphite, 0.3 parts of divinylbenzene, 8 parts of modified glass fiber, 1 part of antioxidant, and 0.8 parts of lubricant; wherein the modified monomer is 2-phenylacrylic acid; the modified glass fiber is prepared by Preparation Example 1; the antioxidant is antioxidant 1010; and the lubricant is polyethylene wax.

[0076] A method for preparing a high-strength mesh cloth, characterized in that it comprises the following steps:

[0077] S1. Weigh caprolactam, p-phenylenediamine, adipic acid, biphenyl dicarboxylic acid, modified monomer, zinc diethyl phosphite, divinylbenzene, modified glass fiber, antioxidant, and lubricant by weight for later use;

[0078] S2, caprolactam, p-phenylenediamine, 1 / 2 of the mass of adipic acid, biphenyl dicarboxylic acid, and modified monomers are added to a polymerization kettle, the stirring speed is controlled to 500r / min, stirring and mixing for 40min, vacuumizing, heating to 226°C under nitrogen environment, reacting for 7h, depressurizing to normal pressure, adding the remaining adipic acid, modified glass fiber, diethyl zinc hypophosphite, and divinylbenzene, heating to 242°C, and continuing to react for 5h. After the reaction is completed, the discharged material is cooled to obtain a polyamide copolymer;

[0079] S3. Mix the polyamide copolymer, antioxidant and lubricant and stir for 40 minutes to obtain a mixture, control the melting temperature to 245°C, the spinning temperature to 250°C, the spinning speed to 850m / min, the pulling speed to 450m / min, the pulling multiple to 4 times, melt-extrude the mixture and then spin it into shape, pull and stretch it to obtain nylon fibers, twist the nylon fibers to form nylon braided wire, and weave the nylon braided wire with a plain weave structure to obtain a high-strength mesh.

[0080] Comparative Example 2

[0081] Comparative Example 2 is different from Example 1 only in that the modified monomer is only 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester, which is as follows:

[0082] A high-strength mesh cloth comprises the following raw materials in parts by weight: 24 parts of caprolactam, 12 parts of p-phenylenediamine, 38 parts of adipic acid, 15 parts of biphenyl dicarboxylic acid, 4.5 parts of modified monomer, 0.5 parts of diethyl zinc hypophosphite, 0.3 parts of divinylbenzene, 8 parts of modified glass fiber, 1 part of antioxidant, and 0.8 parts of lubricant; wherein the modified monomer is 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester; the modified glass fiber is prepared by Preparation Example 1; the antioxidant is antioxidant 1010; and the lubricant is polyethylene wax.

[0083] A method for preparing a high-strength mesh cloth, characterized in that it comprises the following steps:

[0084] S1. Weigh caprolactam, p-phenylenediamine, adipic acid, biphenyl dicarboxylic acid, modified monomer, zinc diethyl phosphite, divinylbenzene, modified glass fiber, antioxidant, and lubricant by weight for later use;

[0085] S2, caprolactam, p-phenylenediamine, 1 / 2 of the mass of adipic acid, biphenyl dicarboxylic acid, and modified monomers are added to a polymerization kettle, the stirring speed is controlled to 500r / min, stirring and mixing for 40min, vacuumizing, heating to 226°C under nitrogen environment, reacting for 7h, depressurizing to normal pressure, adding the remaining adipic acid, modified glass fiber, diethyl zinc hypophosphite, and divinylbenzene, heating to 242°C, and continuing to react for 5h. After the reaction is completed, the discharged material is cooled to obtain a polyamide copolymer;

[0086] S3. Mix the polyamide copolymer, antioxidant and lubricant and stir for 40 minutes to obtain a mixture, control the melting temperature to 245°C, the spinning temperature to 250°C, the spinning speed to 850m / min, the pulling speed to 450m / min, the pulling multiple to 4 times, melt-extrude the mixture and then spin it into shape, pull and stretch it to obtain nylon fibers, twist the nylon fibers to form nylon braided wire, and weave the nylon braided wire with a plain weave structure to obtain a high-strength mesh.

[0087] Comparative Example 3

[0088] Comparative Example 3 is different from Example 1 only in that the modified glass fiber prepared in Preparation Example 1 is replaced by the modified glass fiber prepared in Comparative Preparation Example 1, as follows:

[0089] A high-strength mesh cloth comprises the following raw materials in parts by weight: 24 parts of caprolactam, 12 parts of p-phenylenediamine, 38 parts of adipic acid, 15 parts of biphenyl dicarboxylic acid, 4.5 parts of modified monomer, 0.5 parts of diethyl zinc hypophosphite, 0.3 parts of divinylbenzene, 8 parts of modified glass fiber, 1 part of antioxidant, and 0.8 parts of lubricant; wherein the modified monomer comprises 2-phenylacrylic acid and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester in a mass ratio of 3:1; the modified glass fiber is prepared by comparative preparation example 1; the antioxidant is antioxidant 1010; and the lubricant is polyethylene wax.

[0090] A method for preparing a high-strength mesh cloth, characterized in that it comprises the following steps:

[0091] S1. Weigh caprolactam, p-phenylenediamine, adipic acid, biphenyl dicarboxylic acid, modified monomer, zinc diethyl phosphite, divinylbenzene, modified glass fiber, antioxidant, and lubricant by weight for later use;

[0092] S2, caprolactam, p-phenylenediamine, 1 / 2 of the mass of adipic acid, biphenyl dicarboxylic acid, and modified monomers are added to a polymerization kettle, the stirring speed is controlled to 500r / min, stirring and mixing for 40min, vacuumizing, heating to 226°C under nitrogen environment, reacting for 7h, depressurizing to normal pressure, adding the remaining adipic acid, modified glass fiber, diethyl zinc hypophosphite, and divinylbenzene, heating to 242°C, and continuing to react for 5h. After the reaction is completed, the discharged material is cooled to obtain a polyamide copolymer;

[0093] S3. Mix the polyamide copolymer, antioxidant and lubricant and stir for 40 minutes to obtain a mixture, control the melting temperature to 245°C, the spinning temperature to 250°C, the spinning speed to 850m / min, the pulling speed to 450m / min, the pulling multiple to 4 times, melt-extrude the mixture and then spin it into shape, pull and stretch it to obtain nylon fibers, twist the nylon fibers to form nylon braided wire, and weave the nylon braided wire with a plain weave structure to obtain a high-strength mesh.

[0094] Comparative Example 4

[0095] Comparative Example 4 is different from Example 1 only in that the modified glass fiber prepared in Preparation Example 1 is replaced by the modified glass fiber prepared in Comparative Preparation Example 2, as follows:

[0096] A high-strength mesh cloth comprises the following raw materials in parts by weight: 24 parts of caprolactam, 12 parts of p-phenylenediamine, 38 parts of adipic acid, 15 parts of biphenyl dicarboxylic acid, 4.5 parts of modified monomer, 0.5 parts of diethyl zinc hypophosphite, 0.3 parts of divinylbenzene, 8 parts of modified glass fiber, 1 part of antioxidant, and 0.8 parts of lubricant; wherein the modified monomer comprises 2-phenylacrylic acid and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester in a mass ratio of 3:1; the modified glass fiber is prepared by comparative preparation example 2; the antioxidant is antioxidant 1010; and the lubricant is polyethylene wax.

[0097] A method for preparing a high-strength mesh cloth, characterized in that it comprises the following steps:

[0098] S1. Weigh caprolactam, p-phenylenediamine, adipic acid, biphenyl dicarboxylic acid, modified monomer, zinc diethyl phosphite, divinylbenzene, modified glass fiber, antioxidant, and lubricant by weight for later use;

[0099] S2, caprolactam, p-phenylenediamine, 1 / 2 of the mass of adipic acid, biphenyl dicarboxylic acid, and modified monomers are added to a polymerization kettle, the stirring speed is controlled to 500r / min, stirring and mixing for 40min, vacuumizing, heating to 226°C under nitrogen environment, reacting for 7h, depressurizing to normal pressure, adding the remaining adipic acid, modified glass fiber, diethyl zinc hypophosphite, and divinylbenzene, heating to 242°C, and continuing to react for 5h. After the reaction is completed, the discharged material is cooled to obtain a polyamide copolymer;

[0100] S3. Mix the polyamide copolymer, antioxidant and lubricant and stir for 40 minutes to obtain a mixture, control the melting temperature to 245°C, the spinning temperature to 250°C, the spinning speed to 850m / min, the pulling speed to 450m / min, the pulling multiple to 4 times, melt-extrude the mixture and then spin it into shape, pull and stretch it to obtain nylon fibers, twist the nylon fibers to form nylon braided wire, and weave the nylon braided wire with a plain weave structure to obtain a high-strength mesh.

[0101] Comparative Example 5

[0102] Comparative Example 5 is different from Example 1 only in that the modified glass fiber prepared in Preparation Example 1 is replaced by the modified glass fiber prepared in Comparative Preparation Example 3, as follows:

[0103] A high-strength mesh cloth comprises the following raw materials in parts by weight: 24 parts of caprolactam, 12 parts of p-phenylenediamine, 38 parts of adipic acid, 15 parts of biphenyl dicarboxylic acid, 4.5 parts of modified monomer, 0.5 parts of diethyl zinc hypophosphite, 0.3 parts of divinylbenzene, 8 parts of modified glass fiber, 1 part of antioxidant, and 0.8 parts of lubricant; wherein the modified monomer comprises 2-phenylacrylic acid and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester in a mass ratio of 3:1; the modified glass fiber is prepared by comparative preparation example 3; the antioxidant is antioxidant 1010; and the lubricant is polyethylene wax.

[0104] A method for preparing a high-strength mesh cloth, characterized in that it comprises the following steps:

[0105] S1. Weigh caprolactam, p-phenylenediamine, adipic acid, biphenyl dicarboxylic acid, modified monomer, zinc diethyl phosphite, divinylbenzene, modified glass fiber, antioxidant, and lubricant by weight for later use;

[0106] S2, caprolactam, p-phenylenediamine, 1 / 2 of the mass of adipic acid, biphenyl dicarboxylic acid, and modified monomers are added to a polymerization kettle, the stirring speed is controlled to 500r / min, stirring and mixing for 40min, vacuumizing, heating to 226°C under nitrogen environment, reacting for 7h, depressurizing to normal pressure, adding the remaining adipic acid, modified glass fiber, diethyl zinc hypophosphite, and divinylbenzene, heating to 242°C, and continuing to react for 5h. After the reaction is completed, the discharged material is cooled to obtain a polyamide copolymer;

[0107] S3. Mix the polyamide copolymer, antioxidant and lubricant and stir for 40 minutes to obtain a mixture, control the melting temperature to 245°C, the spinning temperature to 250°C, the spinning speed to 850m / min, the pulling speed to 450m / min, the pulling multiple to 4 times, melt-extrude the mixture and then spin it into shape, pull and stretch it to obtain nylon fibers, twist the nylon fibers to form nylon braided wire, and weave the nylon braided wire with a plain weave structure to obtain a high-strength mesh.

[0108] Comparative Example 6

[0109] Comparative Example 6 is different from Example 1 only in that the mass of p-phenylenediamine is replaced by caprolactam, as follows:

[0110] A high-strength mesh cloth comprises the following raw materials in parts by weight: 36 parts of caprolactam, 38 parts of adipic acid, 15 parts of biphenyl dicarboxylic acid, 4.5 parts of modified monomers, 0.5 parts of diethyl zinc hypophosphite, 0.3 parts of divinylbenzene, 8 parts of modified glass fibers, 1 part of antioxidant, and 0.8 parts of lubricant; wherein the modified monomers comprise 2-phenylacrylic acid and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester in a mass ratio of 3:1; the modified glass fibers are prepared by Preparation Example 1; the antioxidant is antioxidant 1010; and the lubricant is polyethylene wax.

[0111] A method for preparing a high-strength mesh cloth, characterized in that it comprises the following steps:

[0112] S1. Weigh caprolactam, adipic acid, biphenyl dicarboxylic acid, modified monomer, zinc diethyl phosphite, divinylbenzene, modified glass fiber, antioxidant, and lubricant by weight for later use;

[0113] S2, caprolactam, 1 / 2 of the mass of adipic acid, biphenyl dicarboxylic acid, and modified monomers are added to a polymerization kettle, the stirring speed is controlled to 500r / min, and the mixture is stirred and mixed for 40min, and then vacuumed, heated to 226°C under a nitrogen environment, reacted for 7h, and depressurized to normal pressure, and the remaining adipic acid, modified glass fiber, diethyl zinc hypophosphite, and divinylbenzene are added, and the temperature is raised to 242°C, and the reaction is continued for 5h. After the reaction is completed, the discharged material is cooled to obtain a polyamide copolymer;

[0114] S3. Mix the polyamide copolymer, antioxidant and lubricant and stir for 40 minutes to obtain a mixture, control the melting temperature to 245°C, the spinning temperature to 250°C, the spinning speed to 850m / min, the pulling speed to 450m / min, the pulling multiple to 4 times, melt-extrude the mixture and then spin it into shape, pull and stretch it to obtain nylon fibers, twist the nylon fibers to form nylon braided wire, and weave the nylon braided wire with a plain weave structure to obtain a high-strength mesh.

[0115] Comparative Example 7

[0116] Comparative Example 7 is different from Example 1 only in that the mass of biphenyl dicarboxylic acid is replaced by adipic acid, as follows:

[0117] A high-strength mesh cloth comprises the following raw materials in parts by weight: 24 parts of caprolactam, 12 parts of p-phenylenediamine, 53 parts of adipic acid, 4.5 parts of modified monomers, 0.5 parts of diethyl zinc hypophosphite, 0.3 parts of divinylbenzene, 8 parts of modified glass fibers, 1 part of antioxidant, and 0.8 parts of lubricant; wherein the modified monomers comprise 2-phenylacrylic acid and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester in a mass ratio of 3:1; the modified glass fibers are prepared by Preparation Example 1; the antioxidant is antioxidant 1010; and the lubricant is polyethylene wax.

[0118] A method for preparing a high-strength mesh cloth, characterized in that it comprises the following steps:

[0119] S1. Weigh caprolactam, p-phenylenediamine, adipic acid, modified monomer, zinc diethylphosphite, divinylbenzene, modified glass fiber, antioxidant, and lubricant by weight for later use;

[0120] S2, caprolactam, p-phenylenediamine, 1 / 2 of the mass of adipic acid and modified monomer are added to a polymerization kettle, the stirring speed is controlled to 500r / min, stirring and mixing for 40min, vacuumizing, heating to 226°C under nitrogen environment, reacting for 7h, depressurizing to normal pressure, adding the remaining adipic acid, modified glass fiber, diethyl zinc hypophosphite and divinylbenzene, heating to 242°C, continuing to react for 5h, and cooling the discharged material after the reaction is completed to obtain a polyamide copolymer;

[0121] S3. Mix the polyamide copolymer, antioxidant and lubricant and stir for 40 minutes to obtain a mixture, control the melting temperature to 245°C, the spinning temperature to 250°C, the spinning speed to 850m / min, the pulling speed to 450m / min, the pulling multiple to 4 times, melt-extrude the mixture and then spin it into shape, pull and stretch it to obtain nylon fibers, twist the nylon fibers to form nylon braided wire, and weave the nylon braided wire with a plain weave structure to obtain a high-strength mesh.

[0122] Performance Testing

[0123] The fiber density of the nylon fibers obtained in Control Examples 1-3 and Comparative Examples 1-7 was 1.2 g / cm 3 ; The linear density of nylon braided wire is 0.18g / cm and the diameter is 5mm; the mesh density of high-strength mesh is 1980 mesh / 100cm 2 , prepare the nylon fiber sample to be tested, the nylon braided wire sample to be tested and the high-strength mesh cloth sample to be tested; and perform the following performance tests respectively:

[0124] The breaking strength of nylon fiber is tested according to the national standard GB / T 4344-2008 "Test method for tensile properties of chemical fiber filaments", with a stretching distance of 500mm and a stretching speed of 500mm / min.

[0125] The breaking strength of nylon braided wire is tested according to the national standard GB / T 8834-2016 "Determination of physical and mechanical properties of fiber ropes";

[0126] The bursting strength of high-strength mesh is tested in accordance with the national standard GB / T 19976-2005 "Determination of bursting strength of textiles - Steel ball method";

[0127] Aging resistance: The high-strength mesh sample to be tested is stretched and fixed on a bracket, placed in an 80W UV light box to receive direct UV light for 240 hours, and the bursting strength retention rate after UV light irradiation is tested at a temperature of 25°C and a relative humidity of 45%;

[0128] High temperature and high humidity resistance: The high-strength mesh sample to be tested is first placed in a constant temperature and humidity environment at 25°C and 100% relative humidity for 24 hours, then placed in an environment at 180°C for 240 hours, and the bursting strength retention rate after high temperature and high humidity treatment is tested in an environment at 25°C and 45% relative humidity;

[0129] The test results are shown in Table 1

[0130] Table 1:

[0131]

[0132] It can be seen from the data shown in Table 1 above that the comprehensive performance of the high-strength mesh obtained in Examples 1-3 is significantly better than that in Comparative Examples 1-7. The high-strength mesh has high comprehensive mechanical strength, good resistance to ultraviolet aging and high temperature and humidity, and is suitable for application in high-performance requirements such as construction materials and special protective equipment. It has high practicality and broad application prospects.

[0133] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A high-strength mesh, characterized in that: The invention comprises the following raw materials in parts by weight: 24-32 parts of caprolactam, 12-18 parts of p-phenylenediamine, 38-45 parts of adipic acid, 15-20 parts of biphenyl dicarboxylic acid, 4.5-6.5 parts of modified monomer, 0.5-1 part of diethyl zinc hypophosphite, 0.3-0.8 part of divinylbenzene, 8-12 parts of modified glass fiber, 1-2 parts of antioxidant and 0.8-1.2 parts of lubricant.

2. The high-strength mesh according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 28 parts of caprolactam, 15 parts of p-phenylenediamine, 42 parts of adipic acid, 18 parts of biphenyl dicarboxylic acid, 5.5 parts of modified monomer, 0.8 parts of diethyl zinc hypophosphite, 0.5 parts of divinylbenzene, 10 parts of modified glass fiber, 1.5 parts of antioxidant and 1 part of lubricant.

3. The high-strength mesh according to claim 1, characterized in that: The modified monomer comprises 2-phenylacrylic acid and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester in a mass ratio of 3-5:

1.

4. The high-strength mesh according to claim 1, characterized in that: The modified glass fiber is prepared by the following method: (1) adding glass fiber to aminosilane hydrolyzate, stirring for 3-5 hours, washing with water, and drying to obtain amino-treated glass fiber; (2) adding the aminated glass fiber into a phosphorus trichloride-toluene solution, adding 4-dimethylaminopyridine, stirring and treating at a temperature of 78-88° C. for 7-9 hours, removing the solvent under reduced pressure, and vacuum drying to obtain modified glass fiber.

5. The high-strength mesh according to claim 4, characterized in that: In the step (1), the mass ratio of the glass fiber to the aminosilane hydrolyzate is 1:5-7; in the step (2), the mass ratio of the amination glass fiber, the phosphorus trichloride-toluene solution, and the 4-dimethylaminopyridine is 10:30-50:1-2; and in the phosphorus trichloride-toluene solution, the volume ratio of phosphorus trichloride to toluene is 2-3:4-8.

6. The high-strength mesh according to claim 4, characterized in that: The aminosilane hydrolyzate in step (1) is prepared by the following method: γ-aminopropyltriethoxysilane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane are added to an ethanol solution, and stirred at a temperature of 50-70° C. for 1-2 hours to obtain an aminosilane hydrolyzate.

7. The high-strength mesh according to claim 6, characterized in that: The mass ratio of the gamma-aminopropyltriethoxysilane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and the ethanol solution is 7:2-3:100; and the mass concentration of the ethanol solution is 65-85%.

8. The high-strength mesh cloth according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1010, antioxidant 1098, and antioxidant 168; the lubricant is at least one of polyethylene wax, calcium stearate, and zinc stearate.

9. A method for preparing the high-strength mesh cloth according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Weigh caprolactam, p-phenylenediamine, adipic acid, biphenyl dicarboxylic acid, modified monomer, zinc diethyl phosphite, divinylbenzene, modified glass fiber, antioxidant, and lubricant by weight for later use; S2, caprolactam, p-phenylenediamine, 1 / 2 mass of adipic acid, biphenyl dicarboxylic acid, and modified monomer are added to a polymerization kettle, stirred and mixed, vacuumed, heated to 226-235°C under a protective gas environment, reacted for 5-7h, depressurized to normal pressure, added with remaining adipic acid, modified glass fiber, zinc diethyl hypophosphite, and divinylbenzene, heated to 242-248°C, and continued to react for 3-5h. After the reaction, the discharged material is cooled to obtain a polyamide copolymer; S3, mixing a polyamide copolymer, an antioxidant, and a lubricant, melt-extrude, spin-form, and draw and stretch to obtain nylon fibers, twist the nylon fibers to form nylon braided wires, and braid the nylon braided wires to obtain a high-strength mesh.

10. The method for preparing the high-strength mesh cloth according to claim 9, characterized in that: In step S3, the melting temperature is 245-255° C., the spinning temperature is 250-260° C., the spinning speed is 850-1050 m / min, the drawing speed is 450-650 m / min, and the drawing multiple is 4-6 times.

Citation Information

Cited By

  • High-wear-resistance modified nylon-based material and preparation method thereof

    CN120349613A

  • A high wear resistant modified nylon-based material and a method of making the same

    CN120349613B